2019
DOI: 10.1111/ddi.12883
|View full text |Cite
|
Sign up to set email alerts
|

Integration of physiological knowledge into hybrid species distribution modelling to improve forecast of distributional shifts of tropical corals

Abstract: Aim: Predicting species distributional shifts in future climate scenarios representing conditions that do not exist in the current world is a challenge. Species distribution models may result in misrepresented projections for species living in extreme conditions if based on truncated response functions. Model extrapolation may not detect declines that could occur if future environment conditions exceeded the physiological tolerance of the species. We developed a novel method aimed to overcome this constrain by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 79 publications
(107 reference statements)
1
35
0
Order By: Relevance
“…To assess these shortcomings, we need more manipulative experiments characterizing species' fundamental niches (Guisan & Thuiller, 2005;Kearney & Porter, 2009;Peterson & Soberón, 2012). Recent studies have found that integrating mechanistic and correlative models is a key step in predicting species distributions and range dynamics, especially in the complex context of a rapidly changing climate Kotta et al, 2019;Rodríguez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To assess these shortcomings, we need more manipulative experiments characterizing species' fundamental niches (Guisan & Thuiller, 2005;Kearney & Porter, 2009;Peterson & Soberón, 2012). Recent studies have found that integrating mechanistic and correlative models is a key step in predicting species distributions and range dynamics, especially in the complex context of a rapidly changing climate Kotta et al, 2019;Rodríguez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, this suggests that the habitat will not be adequate according to the values used within the training data. Obviously, the incorporation of other sources of information, e.g., physiological and genetic adaptation of corals, dispersal and species interactions, or the effects of local anthropogenic disturbances, would improve the reliability of SDMs projections (Diniz‐filho et al., 2019; Donner, 2009; Gardner & Gaston, 2019; Rodriguez, Garcia, et al., 2019; Singer, Schweiger, Kühn, & Johst, 2018). Likewise, corals' symbionts can differ among species and play an important role in corals adaptation (Baker, Starger, McClanahan, & Glynn, 2004; Rodríguez et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of areas where corals can be most affected by these environmental changes is key for adequate conservation plans. Within this context, only few studies have aimed to predict changes, under climate change scenarios, in the distribution of corals (Chefaoui, Casado‐Amezúa, & Templado, 2017; Guinan, Brown, Dolan, & Grehan, 2009; Tittensor et al., 2009; Woodby, Carlile, & Hulbert, 2009), including tropical corals (Couce, Ridgwell, & Hendy, 2013; Franklin, Jokiel, & Donahue, 2013; Freeman, Kleypas, & Miller, 2013; Rodriguez, Garcia, Carreño, & Martínez, 2019; Rodriguez, Martínez, & Tuya, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For eucalypts, these models can include the direct impacts of increasing carbon dioxide levels on growth (Battaglia, Bruce, Brack, & Baker, 2009), which cannot easily be simulated using SDM methods. For instance, Rodriguez, Garcia, Carreno, and Martinez (2019) have used a hybrid model including physiological knowledge to improve predictions of distributional shifts of a coral species under climate change made using the Maxent SDM. The hybrid model predicted potential expansion to higher latitudes, which agreed with some recent observations from the Canary Islands (Clemente et al, 2010; Box).…”
Section: Climate Change Impacts On Distributionsmentioning
confidence: 99%